(untitled) (Bangladesh Journal of Medical Science, 2012)
Demographic and epidemiological transitions reveal geriatric problems as burning public health issue. The present cross-sectional study was undertaken to explore the health awareness among geriatric people in Mirpur in Dhaka city from January to April 2008 on purposively selected persons aged 60 years and above. An interviewer administered semi-structured questionnaire was used for data collection. The mean age of the respondents was found to be 66.5 ±7.25 yrs (Range: 60-103 yrs). It was found that perfect knowledge about food, nutrition, health and disease is significantly high among male respondents. The study revealed that 13.3% and 12.8% respondents have perfect knowledge on balanced diet and fiber containing food for regular bowel movement respectively. A large number of respondents (40.6%) were found having no knowledge about osteoporosis preventing foods. It was also found that 38.0% and 22.6% respondents have no knowledge regarding the causes of gingivitis and helminthasis respectively. On the basis of significant findings, it was suggested that more emphasis should be given on health education and awareness among geriatric people in order to ensure physical, mental and socially sound health. DOI: http://dx.doi.org/10.3329/bjms.v10i4.9497 BJMS 2011; 10 (4): 260-265